2013
DOI: 10.1002/hep.26153
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of tumor-associated antigen-specific T cell responses by radiofrequency ablation of hepatocellular carcinoma

Abstract: Radiofrequency ablation (RFA) is one of the treatments for hepatocellular carcinoma (HCC) and is known to enhance host immune response. However, the epitopes to which enhanced immune responses occur, the impact on patient prognosis, and the functions and phenotype of T cells induced are still unclear. To address these issues, we analyzed immune responses before and after RFA in 69 HCC patients using 11 tumor-associated antigen (TAA)-derived peptides that we identified to be appropriate to analyze HCC-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
185
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(196 citation statements)
references
References 38 publications
11
185
0
Order By: Relevance
“…Increases have been reported in the frequency of TAA-specific T cells after treatments for HCC such as RFA and TACE [9,10]. In the present study, we found an MDSCs [11,12].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Increases have been reported in the frequency of TAA-specific T cells after treatments for HCC such as RFA and TACE [9,10]. In the present study, we found an MDSCs [11,12].…”
Section: Discussionsupporting
confidence: 70%
“…For example, HCC treatments with RFA or TACE were found to increase the frequency of tumor-associated antigen (TAA)-specific T cells due to the creation of an antigen source by the destruction of tumor cells [9,10]. In addition, recent studies demonstrated that beyond their direct cytotoxic effects on cancer cells, several conventional chemotherapeutic drugs promoted the elimination or inactivation of regulatory T cells (Tregs) or myeloid-derived suppressor cells (MDSCs), resulting in enhanced host antitumor immunity [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with solitary lesions appear to have benefited more than patients with multiple lesions, which may be explained by the rapid pharmacokinetics of LTLD (19) along with prolonged RFA heating. Longer heating appears to increase local tissue concentration of doxorubicin released from LTLD (24) and heating may also trigger a local T-cell response (30). In patients with multiple lesions, the time needed to reposition the probe and initiate the ablation would lose the high serum concentration of LTLD due to relatively rapid clearance.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation may explain why the addition of LTLD to RFA had no impact on outcomes in the overall population. Dexamethasone, which was administered in the LTLD arm to prevent type I hypersensitivity, could have blunted the postablation inflammatory and immune T-cell response (30). This could be particularly true in patients who did not receive a sufficient thermal dose and local LTLD release.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy can destroy cancer cells and enhance tumorassociated antigen presentation (14). However, radiotherapyinduced microenvironmental hypoxia also recruits proinflammatory cells, including TAMs and myeloid-derived suppressor cells (15,16), which can impair the anti-tumor attack enacted by NK or T cells and induce regulatory T cells (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%